Chronic wound sepsis due to retained vacuum assisted closure foam. (24th June 2009) - Beral, Daniel; Adair, Robert; Peckham-Cooper, Adam; Tolan, Damian; Botterill, Ian
Abstract : Count radiolucent foam pieces used in outpatient vacuum assisted wound closure to prevent chronic sepsis